2014
DOI: 10.1080/00380768.2014.907531
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric warming effects on N dynamics and productivity in rice (Oryza sativaL.)

Abstract: Climate warming exhibits strong diurnal variations, with higher warming rates being observed at nighttime, which significantly affects rice (Oryza sativa L.) growth and grain yield. The objective of this study was to determine the effects of asymmetric warming (all-day warming, AW; daytime warming from 07:00 to 19:00, DW; nighttime warming from 19:00 to 07:00, NW, and a control, CK) on rice nitrogen (N) dynamics and productivity. Two rice bucket warming experiments were performed in Nanjing in Jiangsu Province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Crude protein is a conventional expression of the total content of N compounds of the analysed product, calculated by multiplying the corresponding N content by a conversion factor. N content was measured according to micro-Kjeldahl method provided by Xie et al (2018), and the conversion factor for rice grain is 5.95. Amylose content was measured according to the method provided by Hong et al (2004).…”
Section: Experiments Measurementsmentioning
confidence: 99%
“…Crude protein is a conventional expression of the total content of N compounds of the analysed product, calculated by multiplying the corresponding N content by a conversion factor. N content was measured according to micro-Kjeldahl method provided by Xie et al (2018), and the conversion factor for rice grain is 5.95. Amylose content was measured according to the method provided by Hong et al (2004).…”
Section: Experiments Measurementsmentioning
confidence: 99%
“…Apart from these model-based studies, there still exist many in situ studies. For example, Wan et al (2009) revealed that the nocturnal-warming-derived carbon losses in the temperate steppe ecosystem can be compensated by stimulating the following daytime photosynthesis through the depletions of leaf carbohydrates in grassland (Grass) at night; Xie et al (2014) revealed that the increases in the aboveground biomass of rice will be significantly enhanced by asymmetric warming in the jointing stage, but suppressed in the maturity stage; and Phillips et al (2016) suggested that this warming asymmetry would turn the grassland ecosystems into a carbon source, mainly by enhancing the warming-induced carbon losses from unprotected soil.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing bodies of evidence have shown the common existence of significant timelag effects of climate factors on vegetation growth (Braswell et al 1997;Kuzyakov and Gavrichkova 2010;Sherry et al 2008;Wu et al 2015;Zhang et al 2015;Zhao et al 2015). The asymmetric warming is projected to be reinforced (IPCC 2014), which is anticipated to generate enormous effects on the terrestrial green plants' growth (Matiu et al 2016;Peng et al 2013;Su et al 2015;Xie et al 2014). However, little is known about the time-lag effects that asymmetric warming have on different plant biomes.…”
Section: Introductionmentioning
confidence: 99%